2009
DOI: 10.1002/app.31160
|View full text |Cite
|
Sign up to set email alerts
|

Catalyzed chain extension of poly(butylene adipate) and poly(butylene succinate) with 2,2′‐(1,4‐phenylene)‐bis(2‐oxazoline)

Abstract: Low-molecular-weight HOOC-terminated poly(butylene adipate) prepolymer (PrePBA) and poly(butylene succinate) prepolymer (PrePBS) were synthesized through melt-condensation polymerization from adipic acid or succinic acid with butanediol. The catalyzed chain extension of these prepolymers was carried out at 180-220 C with 2,2 0 -(1,4-phenylene)-bis(2-oxazoline) as a chain extender and p-toluenesulfonic acid (p-TSA) as a catalyst. Higher molecular weight polyesters were obtained from the catalyzed chain extensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 28 publications
(25 reference statements)
0
21
0
Order By: Relevance
“…The percentage crystallinity was calculated as: X c = 100Δ H m /Δ H m ° (ΔH m ° = 135 J g −1 for 100% crystalline PBA).…”
Section: Resultsmentioning
confidence: 99%
“…The percentage crystallinity was calculated as: X c = 100Δ H m /Δ H m ° (ΔH m ° = 135 J g −1 for 100% crystalline PBA).…”
Section: Resultsmentioning
confidence: 99%
“…The acid value or amine value was detected using the similar method described in the literature . The number‐average molecular weight of nylon 12 6 was recorded on Agilent 2600 series equipped with a PLgel 5 μm × 100 nm column and a refractive index detector at 25 ° C. N,N‐Dimethylformamide (DMF) was used as the eluent at a flow rate of 1 mL/min and polystyrene was used as the standard.…”
Section: Methodsmentioning
confidence: 99%
“…In order to modify the inferior properties of biodegradable polymer, numerous methods were employed, such as chain extension, nanocomposite, crosslinking, and so on . Chain extension is a commonly swift and efficient method.…”
Section: Introductionmentioning
confidence: 99%
“…Mihai et al employed a multifunctional styrene‐acrylicepoxy copolymer as chain extender to improve the molecular structure and rheology property of PLA, and found that chain extended PLA exhibited obvious strain‐hardening phenomenon, resulting in well foam ability . The catalyzed chain extension of PBS was carried out with 2,2′‐(1,4‐phenylene)‐bis(2‐oxazoline) as a chain extender and p‐toluenesulfonic acid as a catalyst by Huang et al, giving rise to a higher molecular weight and intrinsic viscosity . PBS was chain‐extented with poly (butylene carbonate) using hexamethylene diisocyanate as chain extender, bringing about satisfactory thermal and mechanical properties .…”
Section: Introductionmentioning
confidence: 99%